Smart Farming in Gujarat: The Role of Cloud-Based Technology in Boosting Productivity - Naik Dipan M; Dr. Bhawesh Kumawat (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This study investigates the role of cloud-based technology in enhancing agricultural productivity in Gujarat, focusing on its potential to drive smart farming practices. With agriculture being a cornerstone of Gujarat’s economy, improving farming efficiency through technological advancements is crucial for ensuring sustainable growth and rural development. The study explores key factors such as infrastructure, policy support, and investment requirements that are vital for the widespread adoption of cloud-based smart farming. Additionally, it examines the awareness levels among farmers regarding cloud computing applications like precision farming, weather forecasting, and resource management. Using a mix of qualitative and quantitative methods, including surveys and statistical analysis, the study identifies significant associations between investment, infrastructure, and policy support factors, and farmers' knowledge, sources of information, and perceptions of the benefits of cloud-based technology. The findings suggest that improving internet connectivity, providing financial incentives, and strengthening government policies can significantly increase the adoption of cloud solutions among farmers. This study not only contributes to understanding the current state of smart farming adoption in Gujarat but also provides actionable insights for policymakers, technology providers, and investors to foster a more technologically empowered agricultural sector. The study highlights the societal importance of cloud-based farming in empowering farmers, enhancing food security, promoting sustainable agricultural practices, and driving rural economic growth.
Keywords: Knowledge and Understanding of Cloud-Based Technology; Sources of Information on Cloud-Based Farming; Perceived Benefits of Cloud-Based Farming